2018
DOI: 10.3389/fphar.2018.00153
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Role of Ecto-5′-Nucleotidase/CD73 in Astrocyte Migration by Using Pharmacological Tools

Abstract: CD73 is a bifunctional glycosylphosphatidylinositol (GPI)-anchored membrane protein which functions as ecto-5′-nucleotidase and a membrane receptor for extracellular matrix protein (ECM). A large body of evidence demonstrates a critical involvement of altered purine metabolism and particularly, increased expression of CD73 in a number of human disorders, including cancer and immunodeficiency. Massive up-regulation of CD73 was also found in reactive astrocytes in several experimental models of human neuropathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 96 publications
(156 reference statements)
2
27
0
Order By: Relevance
“…CON is a more globally oriented parameter, while inversion second moment gives information of local changes, especially useful when there are specific changes in enzyme activity on a specific cell type or part of a structure. Immunoblot analysis confirmed increase in protein expression of eN, but it should be noted that besides changes in quantity, catalytic activity of enzyme could change, probably resulting in more AMP to adenosine conversion (Grkovic et al, 2014; Adzic & Nedeljkovic, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…CON is a more globally oriented parameter, while inversion second moment gives information of local changes, especially useful when there are specific changes in enzyme activity on a specific cell type or part of a structure. Immunoblot analysis confirmed increase in protein expression of eN, but it should be noted that besides changes in quantity, catalytic activity of enzyme could change, probably resulting in more AMP to adenosine conversion (Grkovic et al, 2014; Adzic & Nedeljkovic, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that the rate of eN activity does not necessarily correlate with the enzyme protein levels, but rather increases or decreases due to changes in kinetic properties and enzyme efficacy (Stanojevic et al, 2011; Mitrovic et al, 2016, 2017; Grkovic et al, 2018). CD73 also functions as a membrane receptor for extracellular matrix molecules and may participate in a control of cell adhesion and migration, in both normal and neoplastic cells (Sadej et al, 2008; Adzic & Nedeljkovic, 2018). The enzyme has a broad tissue distribution, being expressed in many cell types, including a number of tumor cells (Antonioli et al, 2013 a ).…”
Section: Introductionmentioning
confidence: 99%
“…enzyme [33] which convert AMP to adenosine and which is over-expressed on tumor cells was also studied as part of our collaboration with Innate Pharma company [34].…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the purinoceptors, speci cally the activation of P2Y 6 R in microglial cells promotes the phagocytosis of debris generated by excitotoxic hippocampal damage [51]. Furthermore, NTPDase1/CD39 and eN/CD73 not only that catabolize extracellular ATP and provide adenosine, but function as clusters of differentiation and cell adhesion molecules, which regulate the adhesion and glial cell migration through speci c interactions with extracellular matrix components [52]. Thus, we propose that the up-regulation of NTPDase1/CD39 and eN/CD73 and the change in purinoceptors repertoire induced by TMT are speci c adaptations to the phagocytic activity and amoeboid shape of microglial cells, which migrate along with the wave of spreading neurodegeneration, from hilus towards CA3 and CA1.…”
Section: Discussionmentioning
confidence: 99%